Effect of green clam shells powder addition on properties biodegradable films of polyvinyl alcohol (PVA) - Hendri Hestiawan; Yuzuar Afrizal; Junas Haidi; Candy Juyetzu (Jurnal POLIMESIN, 2023)
This paper presents an experimental study of the addition of green clam shells powder (GCSP) to the biodegradable film properties of polyvinyl alcohol (PVA). To get GCSP, the green clamp shell was immersed in a 50% NaOH solution for 2 hours, blended until the particle size passed 100 mesh, then heated at a temperature of 500 oC for 2 hours. The Biodegradable film characteristic was investigated by the addition of GCSP (2, 4, 8, and 10 %wt) in PVA suspension. PVA/GCSP biodegradable films were prepared by a casting solution method. The GCSP functional group's molecular chemical bond and structural analysis were tested using Fourier Transform Infrared (FTIR) and X-Ray Diffraction (XRD). To obtain the mechanical properties of biodegradable films, a tensile test was carried out. The results of the FTIR and XRD test showed that the alkali treatment or/and the calcination process affected the GCSP grain structure. SEM micrographs showed that the grain structure of GCSP which was treated with alkali or/and the calcination process had a more uniform and homogeneous size. The addition of GCSP to PVA was able to increase the tensile strength of the biodegradable film. Overall, the optimal addition of GCSP was 10 wt.% which was calcination treated in a PVA matrix with tensile strength, elongation at break, and Young's modulus of 170 MPa, 18%, and 1184 MPa, respectively